Characterization of the interaction between platelet factor 4 and homogeneous synthetic low molecular weight heparins. (20th October 2019) - Nguyen, Thi‐Huong; Xu, Yongmei; Brandt, Sven; Mandelkow, Martin; Raschke, Ricarda; Strobel, Ulrike; Delcea, Mihaela; Zhou, Wen; Liu, Jian; Greinacher, Andreas
Abstract: Background: Heparins are usually produced from animal tissues. It is now possible to synthesize heparins. This provides the abilities to overcome shortages of heparin, to optimize biological effects, and to reduce adverse drug effects. Heparins interact with platelet factor 4 (PF4), which can induce an immune response causing thrombocytopenia. This side effect is called heparin‐induced thrombocytopenia (HIT). We characterized the interaction of PF4 and HIT antibodies with oligosaccharides of 6‐, 8‐, 10‐, and 12‐mer size and a hypersulfated 12‐mer (S12‐mer). Methods: We utilized multiple methodologies including isothermal calorimetry, circular dichroism spectroscopy, single molecule force spectroscopy (SMFS), enzyme immunosorbent assay (EIA), and platelet aggregation test to characterize the interaction of synthetic heparin analogs with PF4 and anti‐PF4/heparin antibodies. Results: The synthetic heparin‐like compounds display stronger binding characteristics to PF4 than animal‐derived heparins of corresponding lengths. Upon complexation with PF4, 6‐mer and S12‐mer heparins showed much lower enthalpy, induced less conformational changes in PF4, and interacted with weaker forces than 8‐, 10‐, and 12‐mer heparins. Anti‐PF4/heparin antibodies bind more weakly to complexes formed between PF4 and heparins ≤ 8‐mer than with complexes formed between PF4 and heparins ≥ 10‐mer. Addition of one sulfate group to the 12‐mer resulted in a S12‐mer, which showed substantial changes in its binding characteristics to PF4. Conclusions: We provide a template for characterizing interactions of newly developed heparin‐based anticoagulant drugs with proteins, especially PF4 and the resulting potential antigenicity.